221k views
4 votes
Hey does anyone know the answer to this equation​

Hey does anyone know the answer to this equation​-example-1
User Rayna
by
6.1k points

2 Answers

1 vote

Answer:

C

Explanation:

Substitute the values of x into y and evaluate , that is

x = - 27 → y =
\sqrt[3]{-27} = - 3

x = 0 → y =
\sqrt[3]{0} = 0

x = 27 → y =
\sqrt[3]{27} = 3

The values of y that complete the table are

- 3, 0, 3 → C

User Zasaz
by
6.7k points
4 votes

Answer:

it is D

UR WELCOME

User Volker Seibt
by
5.9k points